2020
DOI: 10.22319/rmcp.v11i4.4950
|View full text |Cite
|
Sign up to set email alerts
|

Acumulación de forraje de Lotus corniculatus L., en función a diferentes estrategias de cosecha

Abstract: El objetivo del estudio fue determinar la mejor estrategia de cosecha en Lotus corniculatus, dependiente de diferentes porcentajes de luz interceptada (LI) por el dosel y una denominada corte fijo (CF) definido estacionalmente, en dos periodos de producción. Los tratamientos (LI y CF) se distribuyeron en un diseño de bloques al azar, con tres repeticiones. El rendimiento de forraje del CF fue 27 % menor al 95 % de LI en el primer periodo (19,915 vs 28,417 kg MS ha-1), y 29 % al promedio de los porcentajes de L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The results obtained coincide with those reported by Álvarez-Vázquez et al [38], whereby the productive evaluation of ectype 202700 showed that the leaf component was 53% of the annual yield, followed by stems with 32%, dry steams 8%, and weeds 7%. Similar values were reported by the same authors in another study, where leaves contributed 56%, stems 30.5%, dry steams 8.5%, and weeds 4.5% [33].…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained coincide with those reported by Álvarez-Vázquez et al [38], whereby the productive evaluation of ectype 202700 showed that the leaf component was 53% of the annual yield, followed by stems with 32%, dry steams 8%, and weeds 7%. Similar values were reported by the same authors in another study, where leaves contributed 56%, stems 30.5%, dry steams 8.5%, and weeds 4.5% [33].…”
Section: Discussionsupporting
confidence: 90%
“…The CIAT 679 material has two propagation methods: seed and stolon (Bastidas et al, 2023). This material can be associated with forage production, if its morpho-physiological characteristics are taken into account, including plant height, leaf:stem ratio, leaf expansion rate, and tiller dynamics (Álvarez et al, 2020;de Dios-León et al, 2022). Cruz-Hernández et al (2017) analyzed two intensities (13-15 and 9-11 cm plant height) of Brachiaria humidicola cv Chetumal and recorded an increase in crude protein and a higher forage accumulation after 28 d of grazing.…”
Section: Introductionmentioning
confidence: 99%